Effects of Acipenserid herpesvirus 2 on the outcome of a Streptococcus iniae co-infection in white sturgeon (Acipenser transmontanus) - Quijano Cardé, Eva Marie; Anenson, Kelsey M.; Yun, Susan; Heckman, Taylor I.; Jungers, Hali T.; Henderson, Eileen E.; Purcell, Sara L.; Fast, Mark; Soto, Esteban (Frontiers in Aquaculture, 2024)
Acipenserid herpesvirus 2 (AciHV-2) is a large double-stranded DNA virus in the family Alloherpesviridae that causes catastrophic outbreaks in young naïve white sturgeon (Acipenser transmontanus) populations, with mortalities of up to 80%. Survivors of these infections are suspected to remain latently infected. The gram-positive zoonotic bacterium Streptococcus iniae is another important sturgeon pathogen that causes severe myositis and up to 50% mortality during natural outbreaks. Throughout the last decade, co-infections of AciHV-2 and S. iniae have been reported in cultured white sturgeon in California resulting in severe presentations of piscine streptococcosis. This phenomenon of herpesvirus and streptococcus co-infection appears to span multiple taxa since in humans, it is recognized that a Human herpesvirus 3 infection (VZV) is a negative prognostic indicator for pediatric Invasive Group A Streptococcal infections (IGASI). While a decrease in humoral immunity caused by VZV has been hypothesized as a potentially important factor in IGASI cases, no natural animal model exists to study this process. Moreover, no studies have investigated these reported co-infections in white sturgeon. Therefore, the goal of this study was to investigate the effects of a recent AciHV-2 infection on the outcome of a subsequent S. iniae challenge in white sturgeon fingerlings. When fish were infected with 108 colony forming units (CFU) of S. iniae intramuscularly (IM), a statistically significant decrease in survival of 41% was detected in the co-infection group compared to the S. iniae group (p-value < 0.001). This difference was not observed when fish were infected with 106 CFU of S. iniae IM. At this lower infection dose, however, a statistically significant downregulation of TNFα was observed in the spleen of fish in the co-infection group compared to the S. iniae group (p-value = 0.0098). Analysis of serum from survivors revealed a statistically significant reduction in anti-S. iniae serum IgM and serum serotransferrin in fish from the co-infection group compared to the S. iniae group (p-value = 0.0134 and p-value = 0.0183, respectively). Further studies are indicated to determine what interactions lead to the decreased production of pathogen-specific IgM, serotransferrin, and TNFα in the host.